2009
DOI: 10.1155/2009/492386
|View full text |Cite
|
Sign up to set email alerts
|

Luteinized Ovarian Thecoma in a Postmenopausal Women Presenting with Virilization

Abstract: We report a case of luteinizing thecoma in a 58-year-old postmenopausal woman who presented with progressive androgenic features and hypertension of one year duration. She did not notice a significant change in her body weight or appetite. Her total serum testosterone level was 4.5 ng/mL. Ultrasound scan revealed a normal-sized uterus and a right-sided solid ovarian mass of 5 cm × 5 cm. Left ovary was normal. She had a total abdominal hysterectomy, bilateral salpingo-oophorectomy, and an omentectomy performed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…According to the MRI findings in the present study, all the thecomas were solid-component masses, regardless of the lesion size, except for one cystic and solid mass, with a pathological diagnosis of luteinized thecoma, which is described in the literature as a rare condition [15]. In another study of 19 patient samples, the authors reported four lesions that presented as mostly cystic masses on cross-sectional imaging [3], which could represent cystic degeneration or stromal edema.…”
Section: Resultsmentioning
confidence: 80%
“…According to the MRI findings in the present study, all the thecomas were solid-component masses, regardless of the lesion size, except for one cystic and solid mass, with a pathological diagnosis of luteinized thecoma, which is described in the literature as a rare condition [15]. In another study of 19 patient samples, the authors reported four lesions that presented as mostly cystic masses on cross-sectional imaging [3], which could represent cystic degeneration or stromal edema.…”
Section: Resultsmentioning
confidence: 80%
“…Das sind seltene von den Thekazellen des Ovars ausgehende endokrin aktive Stromatumoren. Sie treten meist in der Peri-und Postmenopause auf [18]. Ein Anteil von 70% sezerniert Östro-gene, es gibt jedoch auch androgenproduzierende Thekome.…”
Section: Androgenproduzierende Tumoren Des Ovarsunclassified